The Utilization of the Sang Nila Utama Museum as a Resource for Learning History - Ilham Alfads; Danes Jaya Negara; Irawan Irawan (Lembaran Ilmu Kependidikan, 2026)
Background – Museums serve as important educational resources that can support contextual and experiential history learning. The utilization of museums in schools is expected to enhance students’ understanding and engagement in learning history through direct interaction with historical artifacts and information. Purpose – This study aims to describe the utilization of the Sang Nila Utama Museum as a source of history learning at SMA Negeri 6 Pekanbaru, including the learning process, the museum’s readiness, and the constraints encountered in its implementation. Method/approach – This study employed a qualitative approach with a descriptive method. The research subjects consisted of history teachers, tenth-grade students, and the management of the Sang Nila Utama Museum. Data were collected through observation, interviews, and documentation. Data analysis was conducted using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The validity of the data was ensured through source and technique triangulation. Findings – The findings reveal that the Sang Nila Utama Museum has significant potential as a source of history learning because it provides artifact collections and historical information relevant to the learning materials. The implementation of museum-based learning through stages of preparation, collection observation, and reflection was able to increase students’ enthusiasm, participation, and understanding through direct learning experiences. However, several constraints were identified, including limited instructional time, transportation facilities, and the lack of interactive media within the museum environment. Conclusions – The study concludes that the Sang Nila Utama Museum can function effectively as a history learning resource when supported by proper instructional planning and adequate facilities. Museum-based learning contributes positively to students’ historical understanding and learning engagement. Novelty/Originality/Value – This study highlights the practical role of local museums as contextual history learning resources in senior high schools and provides insights into the implementation process, supporting factors, and challenges of museum-based learning in history education.